The effect of caffeine drug on normal rhythmic contractions and on acetylcholin-induced contraction of Rat Ileal smooth muscles - Saad, Khalid H. M. (Al-Mukhtar Journal of Sciences, 1998)
This study was an attempt to know the effect of graded concentrations of caffeine on spontaneous contractions on the ileum smooth muscles of the rat. Caffeine as low as 0.1 mM enhanced rhythmic contractions, and moderate concentrations (1 4 mM) of this drug caused a dose-dependent increase in tension development, while concentrations from (6-9 mM) induced contractions. However the higher concentrations of caffeine (10 mM) up ward caused inhibition of normal spontaneous contractions as well as relaxation of acetylcholine- induced contractions. These results suggest that the excitatory action of the caffeine on this smooth muscle was brought about by increasing calcium influx while the inhibitory effect of high concentrations of the drug may be a result of blocking of inward calcium movement which led to the reduction of free calcium available for contraction.